Proceedings of the 5th Universitas Ahmad Dahlan Public Health Conference (UPHEC 2019) 2020
DOI: 10.2991/ahsr.k.200311.008
|View full text |Cite
|
Sign up to set email alerts
|

High Risk Profile of Pregnancy in Iodine Deficiency Areas

Abstract: High-risk pregnancy, such as abortion, low birth weight, mortality, congenital defects of fetus, disorders of growth and hypothyroidism, might lead to many serious health problems, especially in iodine deficiency disorders (IDD) endemic areas. The aim of this research is to discover high-risk pregnancy profile in iodine deficiency areas. This research used cross-sectional research design. The population and samples were all pregnant mothers settled in research location which was purposively selected based on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Whereas, the prevalence of iodine deficiency worldwide in insufficiency areas was higher (86%) than the prevalence of insufficiency in this research areas [6]. Pregnant women with high-risk pregnancy based on age were 25.1%, this was a higher percentage than found by Supadmi [13]. Additionally, this finding was also different from previous studies that the older age of the maternal, the higher risk of having an insufficient intake of iodine [14], [18].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Whereas, the prevalence of iodine deficiency worldwide in insufficiency areas was higher (86%) than the prevalence of insufficiency in this research areas [6]. Pregnant women with high-risk pregnancy based on age were 25.1%, this was a higher percentage than found by Supadmi [13]. Additionally, this finding was also different from previous studies that the older age of the maternal, the higher risk of having an insufficient intake of iodine [14], [18].…”
Section: Discussioncontrasting
confidence: 65%
“…Pregnant women who live in the coastal areas of Zhejiang had lower UIE than those who live in inland [12]. This research found a higher percentage of insufficient population compared to pregnant women who lived in the deficient area Ponorogo in West Java, Indonesia, namely 59.5% [13]. Patriota added that the prevalence of iodine insufficiency was 53% for women of childbearing age population [6].…”
Section: Discussionmentioning
confidence: 68%